Chlorophyll-ɑ Concentration in the periphyton attached in the PVC substrate submerged in the Air Hitam River, Pekanbaru,Riau Province - Muhammad Ichsan Mulyadi; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPeriphyton is primary producer in the aquatic environment. A research aims to determine the chlorophyll-ɑ concentration contained in the  periphyton that are attached in the submerged PVC substrate has been carried out in April-May 2018 in the Air Hitam River. There were three sampling stations, namely S1 (in the upstream), S2 (in the middle) and S3 (in the downstream). Samplings were conducted once/week for a 3 weeks period. The periphyton samples were brushed from the PVC substrates (8 x 6) cm2. Water quality parameters measured were current speed,temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate,and phosphate content. Results shown that the chlorophyll-ɑ concentration of the periphytonfrom   S1was 1,380 μg/cm²,in S2 was 1,480 μg/cm² and in the S3  was2,026 μg/cm². The water quality parameters were as follows: water current 0.08-0.46 m/s, transparency 18-29 cm, temperature 29-29.30C, dissolved oxygen 3,43-3,56 mg/L, free carbon dioxide 6.2-8.3 mg/L, nitrate 0.29-0.38 mg/L and  phosphate 0.34-0.54 mg/L.Keywords: water quality, trophic state ,oligotrophic, artificial substrate